2016
DOI: 10.11130/jei.2016.31.4.932
|View full text |Cite
|
Sign up to set email alerts
|

Regional Economic Integration and Tax Revenue: East African Community

Abstract: The ultimate goal of regional integration is the long-term high economic growth for member states. Tax revenues are critical to achieving this objective, given the high dependence of developing countries on this fiscal revenue. However, empirical studies have been unable to determine whether regional integration improves or impedes the mobilization of taxes. We use data from 1980 to 2014 in order to estimate a tax model; the results based on the generalized method of moments technique reveal that East African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
4
5
0
3
Order By: Relevance
“…A 1% increase in lagged tax revenue leads to 0.586% increase in tax revenue as a ratio of GDP holding other factors remaining constant. The finding is agrees with (Nnyanzi et al, 2016).…”
Section: Dependent Variable: Lntrsupporting
confidence: 90%
See 1 more Smart Citation
“…A 1% increase in lagged tax revenue leads to 0.586% increase in tax revenue as a ratio of GDP holding other factors remaining constant. The finding is agrees with (Nnyanzi et al, 2016).…”
Section: Dependent Variable: Lntrsupporting
confidence: 90%
“…Here in less developing countries including East Africa higher population in cities are associated with lower incomes because of high cost of living which further leads to low tax revenue collection. The finding is consistent with Addison and Levin (2006) and Becker et al (1999); (Al-Hakami, 2008) and inconsistent with Nnyanzi et al (2016). In urban economy, though better off, offered limited opportunities for revenue generation.…”
Section: Dependent Variable: Lntrsupporting
confidence: 69%
“…Studies that have considered the quality of governance as a determining factor of tax revenue include those of Nnyanzi et al (2016), which analysed the impact of regional integration on tax revenue in the East African Community. The study found a negative and significant relationship between tax revenue and government effectiveness, rule of law and political stability.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Empirical studies on the determinants of tax revenue abound. One strand of the literature finds the level of income, per capita GDP, foreign aid, the share of agriculture, the economic structure, and the degree of openness to be statistically significant in explaining the variations in the revenue to GDP ratio across countries (Addison & Levin, 2012; Gupta, 2007; Nnyanzi, Babyenda, & Bbale, 2016; Zarra‐Nezhad, Ansari, & Moradi, 2016). Another strand of the empirical literature focuses on how institutional variables determine tax revenue.…”
Section: Introductionmentioning
confidence: 99%